CHALLENGES TO SUSTAINABLE SAFE DRINKING WATER: A CASE STUDY OF HILL WATER QUALITY IN RURAL AREA FOR DRINKING PURPOSSES - Impak, Suzan; Mickey, Dodi Pressly; Afiffy, Nur Izzatul; Alisus, Alicetella; Melanie, Marlynn (Applied Research on Civil Engineering and Environment (ARCEE), 2025)
Research on water quality from hill water frequently used by villages for drinking purposes is essential to ensure the health and well-being of rural communities. This research typically focuses on assessing the purity, safety, and contamination levels of water from hill sources that serve as the primary drinking water supply for villages. The investigation includes physical and chemical parameters and other factors that can affect water quality. Studies aim to identify potential sources of contamination, evaluate the effectiveness of existing water treatment systems, and propose solutions to mitigate health risks associated with consuming water from hill sources. Researchers also examine the impact of environmental factors, human activities, seasonal variation, and geographical influences on water quality in these areas. The finding shows that physical and chemical parameters for this area are safe to use as drinking water for the villages. Finding also shows that the potential sources of contamination caused by road construction from uphill. Thus, a design for effective water treatment system proposed as a solution to provide clean water to the villages. By understanding and addressing the challenges related to water quality from hill sources used by villages for drinking purposes, researcher contribute to improving access to safe and clean drinking water, reducing waterborne diseases, and enhancing the overall quality of life in rural communities.